2019
DOI: 10.3389/fnins.2019.01339
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Cofactor Complexes as Building Blocks of Tau Fibrils

Abstract: The aggregation of the human tau protein into neurofibrillary tangles is directly diagnostic of many neurodegenerative conditions termed tauopathies. The species, factors and events that are responsible for the initiation and propagation of tau aggregation are not clearly established, even in a simplified and artificial in vitro system. This motivates the mechanistic study of in vitro aggregation of recombinant tau from soluble to fibrillar forms, for which polyanionic cofactors are the most commonly used exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 50 publications
(91 reference statements)
4
47
0
Order By: Relevance
“…It is likely that most of heparin used to prepare seeds is incorporated into fibrils and a very low amount is expected to be available to induce aggregation of fresh monomers. Fichou et al have shown that Tau fibrils induced by heparin dissociate upon treatment with heparinase concluding that heparin is an essential cofactor of Tau aggregation and a cofactor is required to sustain fibril seeding (Fichou et al, 2018c(Fichou et al, , 2019. However, it appears in our study that Tau seeds without additional heparin are able to stimulate fibril formation but the content of fibrils is limited by the amount of seeds and rapidly reaches a plateau.…”
Section: Discussionmentioning
confidence: 48%
“…It is likely that most of heparin used to prepare seeds is incorporated into fibrils and a very low amount is expected to be available to induce aggregation of fresh monomers. Fichou et al have shown that Tau fibrils induced by heparin dissociate upon treatment with heparinase concluding that heparin is an essential cofactor of Tau aggregation and a cofactor is required to sustain fibril seeding (Fichou et al, 2018c(Fichou et al, , 2019. However, it appears in our study that Tau seeds without additional heparin are able to stimulate fibril formation but the content of fibrils is limited by the amount of seeds and rapidly reaches a plateau.…”
Section: Discussionmentioning
confidence: 48%
“…While these cofactors could be present in the disease brain lysates during the first cycle of amplification, as well as in the mouse brains and in the cultured neurons, they may get diluted in secondary cycles of in vitro amplification. Previous studies have also hypothesized that cofactors could affect tau behavior in in vitro reactions [ 6 , 38 ]. This hypothesis is also consistent with the observation that in the PMCA and QUIC assays, polyanionic factors must be present for multiple cycles of amplifications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that different cofactors can induce differences in tau bril conformation, resulting in distinct properties in a cellular environment. 34,68 We have shown that 2N4R tau bril populations generated using heparin and RNA cofactors have distinct secondary structural compositions. Both heparin and RNA are polyanionic and interact with tau via electrostatic interactions, but differences in the 3-dimensional structure of cofactors may sterically inuence specic tau conformations.…”
Section: The Utility Of Raman Spectroscopy For Identifying Tau Cofactorsmentioning
confidence: 99%